Thesis Submitted to the Department of English in Partial Fulfillment of the Requirements for the Master Degree - Djaalab Fatima Zohra, Guendouz Biya (My University, 2017)
Abstract This work studies George Orwell’s visions of dictatorship in his Nineteen Eighty Four’s novel. Since this research deals with the upheavals of social class struggle, the appropriate approach to apply is the socialist. This latter is based on Marxist literary theory. The aims behind identifying these authoritarian visions are to highlight the negative dimensions of dictatorial regimes and to emphasize their deep influence upon the mass. This research is significant because it raises the readers’ awareness of the contemporary government’s conformity not only to control the physical and concrete aspects of people, but rather to master their psychological and cognitive orientations till they become its property. It can be also a starting point for many researchers, engaged in the same field of our interest, in terms of comparing this interpreted fictional world with today’s world.
Keywords: Marxist literary theory.